Neurogastronomy : how the brain creates flavor and why it matters - Shepherd, Gordon M., 1933- (Columbia University Press, 2012)
Challenging the belief that the sense of smell diminished during human evolution, Shepherd argues that this sense, which constitutes the main component of flavor, is far more powerful and essential than previously believed. --from publisher description.